The Using States of Conciliation Principles to Create Unity in the Kathin Merit-Making Ceremony - Suttajitto, Phramaha Chotniphitphon; Phraratvimolmolee; Kitiwanno, Phrakrubaidika Weang; Sa-ard-iam, Thanarat; Suksen, Phatchavat (Academic MCU Buriram Journal, 2024)
KATHIN: Offering alms to monks is an important practice for the Buddhist community during ceremonies. Ordination is a Buddhist precept and disciplinary practice for monks, who must cooperate and maintain stability in their monastic duties upon receiving ordination according to the discipline of the Buddha. Using moral principles to foster harmony in offering alms is a collective practice of both monks and the Buddhist community in the local community. It involves adhering to the Six Principles of state of conciliation which is a collaborative effort to do good for each other with physical, verbal, and mental kindness, publicly and privately. Sharing blessings, maintaining virtuous conduct, and having mutual understanding contribute to success and harmony, fostering mutual support and avoiding conflicts. This leads to success in various endeavours and ensures peaceful coexistence.